2020
DOI: 10.3329/ijarit.v9i2.45414
|View full text |Cite
|
Sign up to set email alerts
|

Study of growth and productions of tilapia (Oreochromis niloticus) on different population densities in monoculture

Abstract: The experiment was conducted to determine the effects of population densities of tilapia (Oreochromis niloticus) on the growth and production of tilapia in monoculture system. Fish population density was 80 fish per decimal under treatment-I, 160 fish per decimal under treatment-II and 320 fish per decimal under treatment-III. In the ponds under three treatments supplementary feed was not used. The average initial length and weight of the fry of tilapia was 4.48 cm and 0.067 g, respectively. The ponds were fer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…The water transparency values of these ponds were within productive range in the present experiment. Mazid [10], Sharmin et al, [11], Majumder [12], Sarker [13] found more or less similar results. In the present experiment the mean dissolved oxygen values were within suitable range.…”
Section: Growth and Production Performancesmentioning
confidence: 87%
“…The water transparency values of these ponds were within productive range in the present experiment. Mazid [10], Sharmin et al, [11], Majumder [12], Sarker [13] found more or less similar results. In the present experiment the mean dissolved oxygen values were within suitable range.…”
Section: Growth and Production Performancesmentioning
confidence: 87%
“…This value is close to that reported in concrete ponds for the farm of tilapia hatchlings in Costa Rica (6.60) [ 31 ]. The levels of CO 2 may suggest that tilapia populations are at high densities, since at higher density, there is greater accumulation of this compound, which can influence the development of organisms [ 32 ]. Likewise, the analysis of the 10 water samples showed that the level of nitrogenous compounds is above that recommended for tilapia farming [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Higher growth with high stocking density under intensive or semi-intensive farming is the main key point for tilapia monoculture. A stocking density (80-200/decimal or 20,000-50,000/ha) of tilapia in monoculture can be 10-20 times higher than polyculture [54][55][56]. Monoculture production is also dependent on the feeding frequencies, as four times feeding frequency shows a better growth of monosex male tilapia [57].…”
Section: Tilapia Culture In Freshwater Systemsmentioning
confidence: 99%